A medium for rapid cleaning of Aspergillus cleistothecia - Susan G.W. Kaminskyj; John E. Hamer (Fungal Genetics Reports, 1996)
Aspergillus cleistothecia are usually cleaned of adherent Hülle cells by rolling them on an agar surface, which is a tedious process. We have found that incorporating 0.5 - 1.0 % diatomaceious earth (also caled Celite) into 4% agar, as a mild abrasive, helps to speed cleaning about 5-fold (average 10 min reduced to 2 min).